Melamine sponge based on MOF-on-MOF structure and preparation method and application thereof
By in-situ growing Ce-MOF and ZIF-8 on melamine sponge and hydrophobically modifying them, a superhydrophobic/superoleophilic MOF-based melamine sponge was constructed, which solved the problem of the difficulty in separating the hydrophilicity and oleophilicity of melamine sponge, and achieved efficient oil-water separation and dye adsorption, thereby improving the stability and application range of the material.
Patent Information
- Application Number
- CN202511236952.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2025-12-02
AI Technical Summary
Existing melamine sponges are difficult to selectively separate in terms of oil-water separation and dye adsorption due to their hydrophilic and lipophilic properties. Furthermore, existing MOF materials are constrained by bottlenecks such as difficulty in powder forming, mechanical fragility, limited functionality, poor stability in extreme environments, and high-energy-consuming solvothermal processes.
By in-situ growing Ce-MOF and ZIF-8 on melamine sponge and modifying them with methyltrichlorosilane for hydrophobicity, a superhydrophobic/superoleophilic MOF-based melamine sponge was constructed, integrating oil-water separation and dye adsorption functions.
It achieves efficient oil-water separation and dye adsorption, has stable superhydrophobic properties, high oil absorption capacity, separation efficiency of up to 99%, long material life, reduces environmental risks and resource waste, adapts to complex application environments, and improves wastewater treatment efficiency.
Smart Images

Figure CN121041994A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-performance oil-water separation composite materials, specifically relating to a melamine sponge based on a MOF-on-MOF structure, its preparation method, and its application. Background Technology
[0002] Water is a crucial element for sustaining all life. Traditionally, water is considered an inexpensive and abundant resource. However, globally available freshwater resources are extremely scarce. The current state of industrial water pollution is alarming, with textile wastewater and oily wastewater being particularly prominent sources. The textile industry, a traditionally highly polluting sector, generates substantial amounts of wastewater, which is complex in composition, containing dyes, organic and inorganic pollutants, posing a serious threat to human and animal health. Similarly, the discharge of oily wastewater is equally serious. Direct discharge without proper treatment leads to eutrophication, impacting the habitat of aquatic life, water quality, and ultimately disrupting the balance of the entire aquatic ecosystem.
[0003] Three-dimensional porous materials have attracted much attention due to their advantages such as layered networks, high porosity, adjustable pore size, and long permeation channels. Melamine sponges, in particular, are widely used as oil-water separation adsorbents due to their high porosity, high elasticity, lightweight, and ease of mass production. However, their intrinsic hydrophilic and oleophilic nature makes selective oil / water separation difficult, thus requiring surface modification. Existing research has shown that constructing micro-nano rough structures can endow polyurethane sponges with oil-water separation capabilities. For example, CN110387062A achieves a water contact angle of approximately 155° by physically coating silica onto melamine sponges. However, this coating is only fixed by physical adhesion, resulting in weak interfacial bonding. It is easily peeled off under cyclic compression or water erosion, and its function is limited to oil-water separation, failing to handle dye contamination.
[0004] In recent years, emerging porous metal-organic frameworks (MOFs) have shown great application potential in many fields, especially in separation technology. MOFs are constructed by the self-assembly of inorganic metal ions or metal clusters with multifunctional organic linkers. Their unique three-dimensional pore structure, precisely controllable pore size, abundant adsorption sites, ultra-high specific surface area, and excellent porosity make them a popular choice for developing efficient oil-water separation materials and high-performance adsorbents. However, existing MOF oil-water separation materials are still constrained by bottlenecks such as difficulty in powder forming, mechanical fragility, limited functionality, poor stability in extreme environments, and high-energy-consuming solvothermal processes. Summary of the Invention
[0005] This invention aims to address the problems of low dye adsorption efficiency and poor oil-water separation in the fields of industrial wastewater treatment and oil-water separation. It provides a multifunctional superhydrophobic MOF-based melamine sponge based on in-situ growth of Ce-MOF and ZIF-8, and its preparation method. This sponge integrates anion and cationic dye adsorption and oil-water separation. Using a pretreated melamine sponge as a substrate, Ce-MOF and ZIF-8 are sequentially grown in situ on it, and then hydrophobically modified with methyltrichlorosilane (MTS), successfully preparing a superhydrophobic sponge.
[0006] The preparation method of melamine sponge based on MOF-on-MOF structure mainly includes the following steps: (1) Dissolve 1.37 g of cerium ammonium nitrate in 25 mL of deionized water to obtain solution A; dissolve 0.1 g of 2-aminoterephthalic acid in 60 mL of DMF to obtain solution B; pour solution B into solution A and add pretreated melamine sponge; stir in an oil bath at 100 °C for 1 h; then wash three times with DMF and dry at 80 °C for 3 h to obtain Ce-MOF@melamine sponge.
[0007] The mass ratio of 2-aminoterephthalic acid to cerium ammonium nitrate is 1:9.17-20.5. The pretreated melamine sponge is obtained by sonicating in ethanol and deionized water for 1 hour respectively, followed by drying at 60°C. Each sponge has a volume of 1 cm³, and a quantity of 6 sponges is used.
[0008] (2) Dissolve 0.55 g zinc acetate dihydrate in 10 mL of deionized water to obtain solution C; dissolve 6.4 g 2-methylimidazole in 90 mL of deionized water to obtain solution D. Pour solution C into solution D and add Ce-MOF@melamine sponge obtained in step (1). Stir at room temperature for 3 h, wash three times with deionized water, and dry at 40 ℃ for 12 h to obtain ZIF-8@Ce-MOF@melamine sponge.
[0009] The mass ratio of zinc acetate dihydrate to 2-methylimidazole is 1:7.7-17.45.
[0010] (3) Dissolve 1 mL of methyltrichlorosilane in n-hexane, sonicate for 30 min, add the ZIF-8@Ce-MOF@melamine sponge obtained in step (2), continue sonicating for 15-45 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
[0011] The concentration of methyltrichlorosilane in n-hexane is 0.5-1.5 mL / 50 mL.
[0012] The methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge prepared by the above method based on in-situ grown Ce-MOF and ZIF-8 can be used for oil-water separation and dye adsorption.
[0013] Among them, oil-water separation includes the efficient separation of various oils (such as n-hexane, chloroform, benzene, etc.); dye adsorption includes the efficient removal of anionic and cationic dyes (such as methylene blue, malachite green, indigo carmine, etc.).
[0014] The beneficial effects of this invention are: 1. This invention integrates Ce-MOF and ZIF-8 into a melamine sponge substrate through a stepwise in-situ growth process, and further modifies it with hydrophobic methyltrichlorosilane, successfully constructing a novel superhydrophobic / superoleophilic MOF-based melamine sponge that integrates anionic and cationic dye adsorption and oil-water separation functions. This composite structure design fully utilizes the synergistic effect of Ce-MOF and ZIF-8, effectively improving the material's performance in dye adsorption and oil-water separation, and solving the problem that traditional single materials cannot simultaneously and efficiently treat dye wastewater and oil-water mixtures.
[0015] 2. The MTS / ZIF-8@Ce-MOF / melamine sponge in this invention exhibits excellent superhydrophobic properties, with a water contact angle as high as 158°, while also possessing excellent oil absorption capacity and oil-water separation efficiency. Its oil absorption capacity ranges from 36.72-91.35 g / g. After 20 cycles of oil absorption, its hydrophobic properties and oil-water separation ability remain excellent, with a separation efficiency of up to 99%, significantly improving the material's service life and practicality, and reducing replacement costs and resource waste in practical applications.
[0016] 3. This invention employs methyltrichlorosilane and a biocompatible preparation process, avoiding the use of perfluorinated compounds and toxic solvents in traditional preparation processes, thus reducing environmental risks and potential harm to human health. The simple step-by-step in-situ growth method simplifies the preparation process, improves the stability and reproducibility of the material, and provides strong support for its large-scale production and practical application.
[0017] 4. The material of this invention maintains stable superhydrophobic properties under different salt concentrations and pH conditions, with a water contact angle maintained above 153°, exhibiting excellent environmental stability and corrosion resistance. This enables it to adapt to complex practical application environments, such as oil-water separation and dye adsorption in seawater environments, broadening the application range of the material, especially in the fields of marine oil spill accident treatment and coastal industrial wastewater treatment.
[0018] 5. MTS / ZIF-8@Ce-MOF / melamine sponge exhibits high adsorption efficiency for both anionic and cationic dyes, achieving a dye removal rate of up to 94.6% after 140 minutes of settling. Furthermore, the adsorption process conforms to a pseudo-second-order kinetic model, indicating that its adsorption behavior is primarily dominated by chemisorption. This high adsorption capacity gives the material a significant advantage in treating dye wastewater, enabling rapid and effective removal of dye pollutants from water, reducing environmental pollution and ecosystem damage.
[0019] 6. The synergistic effect of Ce-MOF and ZIF-8 not only enhances the adsorption performance of the materials but also enables simultaneous treatment of the oil phase and dyes during adsorption, achieving simultaneous oil-water separation and dye adsorption, thus significantly improving the efficiency and effectiveness of wastewater treatment. This multifunctional integrated design reduces treatment steps and equipment requirements, lowers treatment costs and operational complexity, and provides a simpler and more efficient solution for practical wastewater treatment projects. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the process for preparing superhydrophobic melamine sponge according to the present invention and its related properties.
[0021] Figure 2 The image shows a SEM image of the superhydrophobic melamine sponge obtained in Example 1.
[0022] Figure 3 The XRD spectra of Ce-MOF and ZIF-8 in Example 1 are shown.
[0023] Figure 4 The image shows the water contact angle of the superhydrophobic melamine sponge obtained in Example 1.
[0024] Figure 5 This is a morphology diagram of the cross-section of the superhydrophobic melamine sponge obtained in Example 1.
[0025] Figure 6 The images show the original melamine sponge and the superhydrophobic and superoleophilic melamine sponge obtained in Example 1 in water.
[0026] Figure 7 This is a comparison chart of the adsorption capacity of the superhydrophobic melamine sponge obtained in Example 1 for different organic solvents or oils.
[0027] Figure 8 This is a comparison chart showing the separation efficiency of the superhydrophobic melamine sponge obtained in Example 1 for different organic solvent / water mixtures.
[0028] Figure 9 This is a comparison chart showing the adsorption capacity of the superhydrophobic melamine sponge obtained in Example 1 for n-hexane and chloroform after 20 cycles of adsorption.
[0029] Figure 10 This is a comparison of the transmittance of the superhydrophobic melamine sponge obtained in Example 1 to the three emulsions of water-encapsulated n-hexane, water-encapsulated dichloromethane, and water-encapsulated toluene before and after purification.
[0030] Figure 11 This is a comparison of the ultraviolet spectra of indigo carmine before and after the superhydrophobic melamine sponge obtained in Example 1 adsorbs it.
[0031] Figure 12 This is a comparison of the ultraviolet spectra of the superhydrophobic melamine sponge obtained in Example 1 before and after adsorption of malachite green. Detailed Implementation
[0032] The present invention will be further described below with reference to embodiments, but is not limited thereto.
[0033] Example 1: (1) 1.37 g of cerium ammonium nitrate was dissolved in 25 mL of deionized water to obtain solution A; 0.1 g of 2-aminoterephthalic acid was dissolved in 60 mL of DMF to obtain solution B. Solution B was poured into solution A and 6 pretreated melamine sponges were added. The mixture was stirred in an oil bath at 100 °C for 1 h, then washed three times with DMF and dried at 80 °C for 3 h to obtain Ce-MOF@melamine sponge.
[0034] The pretreated melamine sponge was obtained by sonicating melamine sponges in ethanol and deionized water for 1 hour and then drying them at 60°C. Each sponge had a volume of 1 cm³ and was prepared in quantities of 6.
[0035] (2) Dissolve 0.55 g zinc acetate dihydrate in 10 mL of deionized water to obtain solution C; dissolve 6.4 g 2-methylimidazole in 90 mL of deionized water to obtain solution D. Pour solution C into solution D and add Ce-MOF@melamine sponge. Stir at room temperature for 3 h, then wash three times with deionized water and dry at 40 °C overnight to obtain ZIF-8@Ce-MOF@melamine sponge.
[0036] (3) Dissolve 1 mL of methyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add ZIF-8@Ce-MOF@melamine sponge, continue sonicating for 30 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
[0037] Figure 2This is a SEM image of methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge. The image shows that Ce-MOF is a blocky MOF of approximately 1 μm, while ZIF-8 consists of spherical particles of approximately 0.1 μm, providing a practical basis for loading ZIF-8 onto Ce-MOF.
[0038] Figure 3 The figures show the XRD patterns of Ce-MOF and ZIF-8, respectively. Specifically, Ce-MOF exhibits multiple diffraction peaks at 7.12°, 8.26°, 11.68°, and 24.9°, while ZIF-8 shows characteristic peaks at 7.30°, 10.34°, 12.68°, and 16.42°, which is highly consistent with literature reports. The presence of these characteristic peaks confirms the successful synthesis of Ce-MOF and ZIF-8.
[0039] Figure 4 The modified sponge exhibits a water contact angle of up to 158.2°, both internally and externally. Even after mechanical cutting, water droplets remain spherical on the cut surface. Figure 5 This demonstrates that the superhydrophobic melamine sponge prepared in this invention possesses excellent superhydrophobic properties. There is a significant difference in the behavior of the original melamine sponge and the modified sponge after absorbing water. The original melamine sponge sinks rapidly after absorbing water, while the modified sponge floats on the water surface due to its superhydrophobicity. Figure 6 This characteristic gives it a significant advantage in subsequent oil-water separation applications.
[0040] The modified sponge was immersed in 20 mL of oil or organic solvent (chloroform, n-hexane, octane, dichloromethane, benzene, toluene, petroleum ether, acetone) for saturated adsorption. The mass before and after adsorption was measured, and the adsorption capacity can be calculated according to the following equation: Q = (m1 - m0) / m0 Where m0 and m1 are the masses of the modified sponge before and after adsorption, respectively, and Q is the adsorption capacity.
[0041] Test results are as follows Figure 7 As shown, the modified sponge exhibits excellent adsorption capacity, with an adsorption capacity that can reach 42.12 (n-hexane) to 103.89 (trichloromethane) times its own weight.
[0042] Deionized water and organic solvents (chloroform, n-hexane, octane, dichloromethane, benzene, toluene, petroleum ether) were mixed at a volume ratio of 1:1. A modified sponge was added to adsorb the organic solvents. The mass of deionized water before and after separation was measured. The oil-water separation efficiency can be calculated using the following equation: η=m b / m a Where m a m b η represents the mass of deionized water before and after separation, respectively, and η is the oil-water separation efficiency.
[0043] Test results are as follows Figure 8 As shown, the separation efficiencies of the sponge for chloroform / water, n-hexane / water, benzene / water, petroleum ether / water, n-octane / water, n-heptane / water, and dichloromethane / water are 99.89%, 99.90%, 99.88%, 99.89%, 99.94%, 99.95%, and 99.95%, respectively, proving that the superhydrophobic melamine sponge prepared in this invention has excellent oil-water separation performance.
[0044] The recyclability of the modified sponge was studied through adsorption-desorption experiments. After each adsorption saturation cycle, the sponge was completely compressed and dried before being used in the next cycle. After 20 cycles, the modified sponge still maintained adsorption capacities of 35.62 g / g for hexane and 83.36 g / g for chloroform. Figure 9 Therefore, the superhydrophobic melamine sponge prepared by this invention has excellent durability.
[0045] The purification capabilities of modified sponges for emulsions containing chloroform, hexane, and toluene were investigated through experiments. The specific experimental steps are as follows: A total volume of 56 mL of oil-water mixture (chloroform, n-hexane, toluene) in a volume ratio of 6:1 was mixed, and 0.02 g of Span 80 was added as a surfactant. The mixture was stirred at high speed for 6 hours to prepare three oil-in-water emulsions. A modified sponge was immersed in the three emulsions by external force and stirred to purify the emulsions. The transmittance of each emulsion before and after separation was measured using a UV spectrophotometer. The results are as follows: Figure 10 As shown, the transmittance of each emulsion was greatly improved after treatment with the modified sponge, and all reached over 90%. Therefore, the modified sponge has a highly efficient emulsion purification capability.
[0046] The adsorption and degradation capabilities of common anionic and cationic organic dyes by the original sponge and the modified sponge (both with a volume of 1×1×1 cm³) were compared experimentally. Indigo carmine and malachite green were used as target dyes, respectively. A 25 ppm dye aqueous solution (5 mg dye + 20 mL deionized water) was prepared and allowed to stand for adsorption and degradation. Figure 11 and Figure 12 Experiment (with images showing changes in UV absorbance before and after degradation).
[0047] like Figure 11 and Figure 12As shown, the UV absorbance of all dye solutions decreased significantly after adsorption treatment, and the solution color almost faded, approaching a colorless state. At 140 min, the dye adsorption process reached saturation, with an adsorption efficiency of 94.6% for indigo carmine and 94.1% for malachite green. This result fully confirms that the modified sponge has excellent adsorption effects on both anionic and cationic dyes, indicating that this material has broad application prospects in the field of dye adsorption. It can exhibit excellent adsorption performance for both anionic and cationic dyes, effectively removing dye pollutants and providing a potentially efficient solution for dye wastewater treatment.
[0048] Example 2: (1) 1.10 g of cerium ammonium nitrate was dissolved in 25 mL of deionized water to obtain solution A; 0.1 g of 2-aminoterephthalic acid was dissolved in 60 mL of DMF to obtain solution B. Solution B was poured into solution A and 6 pretreated melamine sponges were added. The mixture was stirred in an oil bath at 100 °C for 1 h, then washed three times with DMF and dried at 80 °C for 3 h to obtain Ce-MOF@melamine sponge.
[0049] (2)-(3) Same as Example 1.
[0050] The modified sponge has a water contact angle of 154°, and adsorption capacities for n-hexane and chloroform are 38.27 g / g and 87.46 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 98.4%, the adsorption efficiency of indigo carmine is 91.3%, and the adsorption efficiency of malachite green solution is 92.3%.
[0051] Example 3: (1) 1.64 g of cerium ammonium nitrate was dissolved in 25 mL of deionized water to obtain solution A; 0.1 g of 2-aminoterephthalic acid was dissolved in 60 mL of DMF to obtain solution B. Solution B was poured into solution A and 6 pretreated melamine sponges were added. The mixture was stirred in an oil bath at 100 °C for 1 h, then washed three times with DMF and dried at 80 °C for 3 h to obtain Ce-MOF@melamine sponge.
[0052] (2)-(3) Same as Example 1.
[0053] The modified sponge has a water contact angle of 156°, and adsorption capacities for n-hexane and chloroform are 37.36 g / g and 89.42 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 97.5%, the adsorption efficiency of indigo carmine is 92.1%, and the adsorption efficiency of malachite green solution is 93.6%.
[0054] Example 4: (1) 1.37 g of cerium ammonium nitrate was dissolved in 25 mL of deionized water to obtain solution A; 0.08 g of 2-aminoterephthalic acid was dissolved in 60 mL of DMF to obtain solution B. Solution B was poured into solution A and 6 pretreated melamine sponges were added. The mixture was stirred in an oil bath at 100 °C for 1 h, then washed three times with DMF and dried at 80 °C for 3 h to obtain Ce-MOF@melamine sponge.
[0055] (2)-(3) Same as Example 1.
[0056] The modified sponge has a water contact angle of 153°, and adsorption capacities for n-hexane and chloroform are 39.67 g / g and 90.01 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 99.5%, the adsorption efficiency of indigo carmine is 90.5%, and the adsorption efficiency of malachite green solution is 93.5%.
[0057] Example 5: (1) 1.37 g of cerium ammonium nitrate was dissolved in 25 mL of deionized water to obtain solution A; 0.12 g of 2-aminoterephthalic acid was dissolved in 60 mL of DMF to obtain solution B. Solution B was poured into solution A and 6 pretreated melamine sponges were added. The mixture was stirred in an oil bath at 100 °C for 1 h, then washed three times with DMF and dried at 80 °C for 3 h to obtain Ce-MOF@melamine sponge.
[0058] (2)-(3) Same as Example 1.
[0059] The modified sponge has a water contact angle of 156°, and adsorption capacities for n-hexane and chloroform are 40.32 g / g and 90.45 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 99.4%, the adsorption efficiency of indigo carmine is 91.4%, and the adsorption efficiency of malachite green solution is 93.3%.
[0060] Example 6: (1) The preparation of Ce-MOF@melamine sponge is the same as in Example 1.
[0061] (2) Dissolve 0.44 g zinc acetate dihydrate in 10 mL of deionized water to obtain solution C; dissolve 6.4 g 2-methylimidazole in 90 mL of deionized water to obtain solution D. Pour solution C into solution D and add Ce-MOF@melamine sponge. Stir at room temperature for 3 h, then wash three times with deionized water and dry at 40 °C overnight to obtain ZIF-8@Ce-MOF@melamine sponge.
[0062] (3) The final superhydrophobic methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge was obtained as in Example 1.
[0063] The modified sponge has a water contact angle of 148°, and adsorption capacities for n-hexane and chloroform are 37.50 g / g and 89.02 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 98.4%, the adsorption efficiency of indigo carmine is 93.4%, and the adsorption efficiency of malachite green solution is 93.5%.
[0064] Example 7: (1) The preparation of Ce-MOF@melamine sponge is the same as in Example 1.
[0065] (2) Dissolve 0.66 g zinc acetate dihydrate in 10 mL of deionized water to obtain solution C; dissolve 6.4 g 2-methylimidazole in 90 mL of deionized water to obtain solution D. Pour solution C into solution D and add Ce-MOF@melamine sponge. Stir at room temperature for 3 h, then wash three times with deionized water and dry at 40 °C overnight to obtain ZIF-8@Ce-MOF@melamine sponge.
[0066] (3) The final superhydrophobic methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge was obtained as in Example 1.
[0067] The modified sponge has a water contact angle of 150°, and adsorption capacities for n-hexane and chloroform are 34.96 g / g and 89.48 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 98.7%, the adsorption efficiency of indigo carmine is 93.6%, and the adsorption efficiency of malachite green solution is 94.0%.
[0068] Example 8: (1) The preparation of Ce-MOF@melamine sponge is the same as in Example 1.
[0069] (2) Dissolve 0.55 g zinc acetate dihydrate in 10 mL of deionized water to obtain solution C; dissolve 5.1 g 2-methylimidazole in 90 mL of deionized water to obtain solution D. Pour solution C into solution D and add Ce-MOF@melamine sponge. Stir at room temperature for 3 h, then wash three times with deionized water and dry at 40 °C overnight to obtain ZIF-8@Ce-MOF@melamine sponge.
[0070] (3) The final superhydrophobic methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge was obtained as in Example 1.
[0071] The modified sponge has a water contact angle of 151°, and adsorption capacities for n-hexane and chloroform are 32.85 g / g and 87.93 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 96.8%, the adsorption efficiency of indigo carmine is 92.4%, and the adsorption efficiency of malachite green solution is 92.5%.
[0072] Example 9: (1) The preparation of Ce-MOF@melamine sponge is the same as in Example 1.
[0073] (2) Dissolve 0.55 g zinc acetate dihydrate in 10 mL of deionized water to obtain solution C; dissolve 7.68 g 2-methylimidazole in 90 mL of deionized water to obtain solution D; pour solution C into solution D and add Ce-MOF@melamine sponge; stir at room temperature for 3 h; wash three times with deionized water; dry at 40 ℃ overnight to obtain ZIF-8@Ce-MOF@melamine sponge.
[0074] (3) The final superhydrophobic methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge was obtained as in Example 1.
[0075] The modified sponge has a water contact angle of 153°, and adsorption capacities for n-hexane and chloroform are 34.17 g / g and 88.62 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 97.5%, the adsorption efficiency of indigo carmine is 93.2%, and the adsorption efficiency of malachite green solution is 93.1%.
[0076] Example 10: (1)-(2) Same as Example 1.
[0077] (3) Dissolve 0.5 mL of methyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add ZIF-8@Ce-MOF@melamine sponge, continue sonicating for 30 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
[0078] The modified sponge has a water contact angle of 153°, and adsorption capacities for n-hexane and chloroform are 40.32 g / g and 89.76 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 98.5%, the adsorption efficiency of indigo carmine is 92.1%, and the adsorption efficiency of malachite green solution is 93.8%.
[0079] Example 11: (1)-(2) Same as Example 1.
[0080] (3) Dissolve 1.5 mL of methyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add ZIF-8@Ce-MOF@melamine sponge, continue sonicating for 30 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
[0081] The modified sponge has a water contact angle of 155°, and adsorption capacities for n-hexane and chloroform are 42.06 g / g and 88.75 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 98.9%, the adsorption efficiency of indigo carmine is 93.2%, and the adsorption efficiency of malachite green solution is 92.6%.
[0082] Example 12: (1)-(2) Same as Example 1.
[0083] (3) Dissolve 1.0 mL of methyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add ZIF-8@Ce-MOF@melamine sponge, continue sonicating for 15 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
[0084] The modified sponge has a water contact angle of 151°, and adsorption capacities for n-hexane and chloroform are 37.83 g / g and 87.65 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 96.2%, the adsorption efficiency of indigo carmine is 93.4%, and the adsorption efficiency of malachite green solution is 91.5%.
[0085] Example 13: (1)-(2) Same as Example 1.
[0086] (3) Dissolve 1.0 mL of methyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add ZIF-8@Ce-MOF@melamine sponge, continue sonicating for 45 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
[0087] The modified sponge has a water contact angle of 156°, and adsorption capacities for n-hexane and chloroform are 41.14 g / g and 90.71 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 99.2%, the adsorption efficiency of indigo carmine is 92.5%, and the adsorption efficiency of malachite green solution is 93.1%.
[0088] Comparative Example 1: (1) 1.37 g of cerium ammonium nitrate was dissolved in 25 mL of deionized water to obtain solution A; 0.1 g of 2-aminoterephthalic acid was dissolved in 60 mL of DMF to obtain solution B. Solution B was poured into solution A and 6 pretreated melamine sponges were added. The mixture was stirred in an oil bath at 100 °C for 1 h, then washed three times with DMF and dried at 80 °C for 3 h to obtain Ce-MOF@melamine sponge.
[0089] (2) Dissolve 1 mL of methyltrichlorosilane in n-hexane, sonicate for 30 min, add 6 Ce-MOF@melamine sponges, sonicate for another 30 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@Ce-MOF@melamine sponge.
[0090] The modified sponge has a water contact angle of 152°, and adsorption capacities for n-hexane and chloroform are 32.56 g / g and 88.14 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 97.5%, the adsorption efficiency of indigo carmine is 72.3%, and the adsorption efficiency of malachite green solution is 72.6%.
[0091] Comparative Example 2: (1) Dissolve 0.55 g zinc acetate dihydrate in 10 mL of deionized water to obtain solution C; dissolve 6.4 g 2-methylimidazole in 90 mL of deionized water to obtain solution D; pour solution C into solution D and add 6 pretreated melamine sponges; stir at room temperature for 3 h; wash three times with deionized water; and dry at 40 °C overnight to obtain ZIF-8@melamine sponge.
[0092] (3) Dissolve 1 mL of methyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add 6 ZIF-8@melamine sponges, sonicate for another 30 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@melamine sponge.
[0093] The modified sponge has a water contact angle of 153°, and adsorption capacities for n-hexane and chloroform are 31.68 g / g and 87.52 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 97.3%, the adsorption efficiency of indigo carmine is 64.8%, and the adsorption efficiency of malachite green solution is 64.3%.
[0094] Comparative Example 3: (1) 1.37 g of cerium ammonium nitrate was dissolved in 25 mL of deionized water to obtain solution A; 0.1 g of 2-aminoterephthalic acid was dissolved in 60 mL of DMF to obtain solution B. Solution B was poured into solution A and 6 pretreated melamine sponges were added. The mixture was stirred in an oil bath at 100 °C for 1 h, then washed three times with DMF and dried at 80 °C for 3 h to obtain Ce-MOF@melamine sponge.
[0095] (2) Dissolve 0.55 g of cobalt nitrate hexahydrate in 10 mL of deionized water to obtain solution C; dissolve 6.4 g of 2-methylimidazole in 90 mL of deionized water to obtain solution D; pour solution C into solution D and add Ce-MOF@melamine sponge; stir at room temperature for 3 h; wash three times with deionized water; dry at 40 °C overnight to obtain ZIF-8@Ce-MOF@melamine sponge.
[0096] (3) Dissolve 1 mL of methyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add ZIF-8@Ce-MOF@melamine sponge, continue sonicating for 30 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
[0097] The modified sponge has a water contact angle of 152°, and adsorption capacities for n-hexane and chloroform are 30.11 g / g and 87.65 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 96.8%, the adsorption efficiency of indigo carmine is 47.8%, and the adsorption efficiency of malachite green solution is 40.9%.
[0098] Comparative Example 4: (1) 1.37 g of nickel nitrate hexahydrate was dissolved in 25 mL of deionized water to obtain solution A; 0.1 g of 2-aminoterephthalic acid was dissolved in 60 mL of DMF to obtain solution B. Solution B was poured into solution A and 6 pretreated melamine sponges were added. The mixture was stirred in an oil bath at 100 °C for 1 h, then washed three times with DMF and dried at 80 °C for 3 h to obtain Ni-MOF@melamine sponge.
[0099] (2) Dissolve 0.55 g zinc acetate dihydrate in 10 mL of deionized water to obtain solution C; dissolve 6.4 g 2-methylimidazole in 90 mL of deionized water to obtain solution D. Pour solution C into solution D and add Ni-MOF@melamine sponge. Stir at room temperature for 3 h, then wash three times with deionized water and dry at 40 °C overnight to obtain ZIF-8@Ni-MOF@melamine sponge.
[0100] (3) Dissolve 1 mL of methyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add ZIF-8@Ni-MOF@melamine sponge, continue sonicating for 30 min, and finally dry at 80 ℃ for 3 h to obtain methyltrichlorosilane@ZIF-8@Ni-MOF@melamine sponge.
[0101] The modified sponge has a water contact angle of 150°, and adsorption capacities for n-hexane and chloroform are 30.98 g / g and 88.63 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 97.5%, the adsorption efficiency of indigo carmine is 51.3%, and the adsorption efficiency of malachite green solution is 53.1%.
[0102] Comparative Example 5: (1)-(2) Same as Example 1 (3) Dissolve 1 mL of octadecyltrichlorosilane in 50 mL of n-hexane, sonicate for 30 min, add the pretreated ZIF-8@Ce-MOF@melamine sponge, sonicate for another 30 min, and finally dry at 80 °C for 3 h to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
[0103] The modified sponge has a water contact angle of 154°, and adsorption capacities for n-hexane and chloroform are 31.65 g / g and 84.32 g / g, respectively. The separation efficiency of the n-hexane / water mixture is 95.4%, the adsorption efficiency of indigo carmine is 90.1%, and the adsorption efficiency of malachite green solution is 89.3%.
[0104] The embodiments described above are merely preferred examples to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the claims.
Claims
1. A melamine sponge based on a MOF-on-MOF structure, characterized in that, The melamine sponge uses pretreated melamine as a substrate, and Ce-MOF and ZIF-8 nanoparticles are sequentially grown in situ onto the pretreated melamine sponge, followed by grafting methyltrichlorosilane to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
2. The melamine sponge based on the MOF-on-MOF structure as described in claim 1, characterized in that, The method for in-situ growth of Ce-MOF nanoparticles onto pretreated melamine sponge is as follows: Cerium ammonium nitrate and 2-aminoterephthalic acid are dissolved in deionized water and DMF, respectively, mixed, and then added to the pretreated melamine sponge. The mixture is stirred in an oil bath, washed, and dried to obtain Ce-MOF@melamine sponge.
3. The melamine sponge based on the MOF-on-MOF structure as described in claim 2, characterized in that, The mass ratio of 2-aminoterephthalic acid to cerium ammonium nitrate was 1:9.17-20.5; the oil bath temperature was 100℃, the stirring time was 1 h, the mixture was washed three times with DMF, and the drying temperature was 80℃.
4. The melamine sponge based on the MOF-on-MOF structure as described in claim 2, characterized in that, The pretreated melamine sponge was obtained by sonicating melamine sponges in ethanol and deionized water for 1 hour and then drying them at 60°C. Each sponge had a volume of 1 cm³ and a quantity of 6 was used.
5. The melamine sponge based on the MOF-on-MOF structure as described in claim 1, characterized in that, The method for in-situ growth of ZIF-8 nanoparticles onto melamine sponge is as follows: zinc acetate dihydrate and 2-methylimidazole are dissolved in deionized water, mixed, and then Ce-MOF / melamine is added. The mixture is stirred, washed, and dried to obtain Ce-MOF@ZIF-8 / melamine.
6. The melamine sponge based on the MOF-on-MOF structure as described in claim 5, characterized in that, The mass ratio of zinc acetate dihydrate to 2-methylimidazole was 1:7.7-17.45; the stirring time was 3 h; the mixture was washed three times with deionized water; and the drying process was carried out at 40 ℃ for 12 h.
7. The melamine sponge based on the MOF-on-MOF structure as described in claim 1, characterized in that, The method for grafting methyltrichlorosilane is as follows: methyltrichlorosilane is mixed with n-hexane and then sonicated. ZIF-8@Ce-MOF@melamine sponge is then added to the mixed solution, and the mixture is sonicated and cured to obtain methyltrichlorosilane@ZIF-8@Ce-MOF@melamine sponge.
8. The melamine sponge based on the MOF-on-MOF structure as described in claim 7, characterized in that, The volume ratio of methyltrichlorosilane to n-hexane is 0.5-1.5:
50. The mixture is sonicated for 30 min, and the sponge is added and sonicated for 15-45 min. The curing is carried out at 80 °C for 3 h.
9. An application of the melamine sponge based on the MOF-on-MOF structure as described in claim 1, characterized in that, The melamine sponge based on the MOF-on-MOF structure is used for dye adsorption and oil-water separation.
10. The application of melamine sponge based on MOF-on-MOF structure as described in claim 9, characterized in that, The dyes are cationic dyes and anionic dyes.
Citation Information
Patent Citations
Super-oleophylic and super-hydrophobic sponge for oil-water separation, and preparation method and application of super-oleophylic and super-hydrophobic sponge
CN110387062A